Intermediate financial accounting. Volume 2 - Arnold, Glenn; Kyle, Suzanne; Athabasca University; Lyryx Learning; BC Open Textbook Project; BCcampus (Lyryx, 2017)
"This text is intended to be the second of two in Intermediate Financial Accounting courses. It presumes that students have already completed the Introductory Financial Accounting, and the first Intermediate Financing Accounting course. The text reflects both current International Financial Reporting Standards (IFRS) and ASPE. This text covers all topics essential to a second level Intermediate Accounting course: current, long-term and complex liabilities, income taxes, pensions, leases, shareholders' equity, earnings per share, statement of cash flows including the direct approach, effects of changes and errors, and disclosures and analysis. Topics that are covered in Advanced Financial Accounting courses, such as consolidations and foreign exchange, are not included here"--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on July 26, 2017).
Keywords: Accounting -- Textbooks; Electronic books